2023
DOI: 10.1002/ohn.272
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Autofluorescence in Pediatric Thyroid Surgery: Experience With False Positive and False Negative Results

Abstract: Devices for near‐infrared light stimulation of autofluorescence (NIRAF) allow for intraoperative identification of parathyroid glands with high sensitivity in adults. However, their performance in the pediatric population is unknown. In this case series with chart review at a tertiary academic children's hospital, we investigated pediatric patients undergoing thyroid surgery and concurrent use of a probe‐based NIRAF device. Thirteen patients (ages 6‐18 years) underwent thyroid and/or neck dissection procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…While near-infrared imaging can aid physicians in identifying parathyroid glands more easily, there remains a risk of identification errors, particularly in cases involving lesions or abnormal anatomical structures. Additionally, limitations may arise when imaging deep-seated tissues, and there may be shortcomings in displaying parathyroid glands covered by the connective tissue membrane [29,30]. Currently, the near-infrared system is influenced by the surgical environment, as evident from our intraoperative observations where electrocautery-induced eschar may interfere with fluorescent signals, consequently affecting imaging quality.…”
Section: Discussionmentioning
confidence: 99%
“…While near-infrared imaging can aid physicians in identifying parathyroid glands more easily, there remains a risk of identification errors, particularly in cases involving lesions or abnormal anatomical structures. Additionally, limitations may arise when imaging deep-seated tissues, and there may be shortcomings in displaying parathyroid glands covered by the connective tissue membrane [29,30]. Currently, the near-infrared system is influenced by the surgical environment, as evident from our intraoperative observations where electrocautery-induced eschar may interfere with fluorescent signals, consequently affecting imaging quality.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found the overall concordance rate of the camera-based NIRAF detection to be at 73%, a stark contrast to the 92.7% accuracy rate of the probe-based PTeye® system documented in the literature. 26 28 This discrepancy suggests that junior surgeons using a probe-based system may inadvertently identify other tissues, such as brown fat, as parathyroids. As a result, our research serves as an essential complement, highlighting the need for standardized practices of near-infrared parathyroid autologous fluorescence technology.…”
Section: Discussionmentioning
confidence: 99%
“…While near-infrared imaging can aid physicians in identifying parathyroid glands more easily, there remains a risk of identi cation errors, particularly in cases involving lesions or abnormal anatomical structures. Additionally, limitations may arise when imaging deep-seated tissues, and there may be shortcomings in displaying parathyroid glands covered by the connective tissue membrane [29][30]. Currently, the near-infrared system is in uenced by the surgical environment, as evident from our intraoperative observations where electrocautery-induced eschar may interfere with uorescent signals, consequently affecting imaging quality.…”
Section: Declarationsmentioning
confidence: 99%